Bacteroides fragilis derived metabolites, identified by molecular networking, decrease Salmonella virulence in mice model - Gautier, Thomas; Oliviero, Nolwenn; Ferron, Solenn; Le Pogam, Pierre; David-Le Gall, Sandrine; Sauvager, Aurélie; Leroyer, Patricia; Cannie, Isabelle; Dion, Sarah; Sweidan, Alaa; Loréal, Olivier; Tomasi, Sophie; et al. (Frontiers in Microbiology, 2022)
In the gut microbiota, resident bacteria prevent pathogens infection by producing specific metabolites. Among bacteria belonging to phylum Bacteroidota, we have previously shown that Bacteroides fragilis or its cell-free supernatant inhibited in vitro Salmonella Heidelberg translocation. In the present study, we have analyzed this supernatant to identify bioactive molecules after extraction and subsequent fractionation using a semi-preparative reversed-phase HPLC. The results indicated that only two fractions (F3 and F4) strongly inhibited S. Heidelberg translocation in a model mimicking the intestinal epithelium. The efficiency of the bioactive fractions was evaluated in BALB/c mice, and the results showed a decrease of S. Heidelberg in Peyer's patches and spleen, associated with a decrease in inflammatory cytokines and neutrophils infiltration. The reduction of the genus Alistipes in mice receiving the fractions could be related to the anti-inflammatory effects of bioactive fractions. Furthermore, these bioactive fractions did not alter the gut microbiota diversity in mice. To further characterize the compounds present in these bioactive fractions, LC-HRMS/MS data were analyzed through molecular networking, highlighting cholic acid (CA) and deoxycholic acid (DCA). In vitro, CA had inhibitory activity against the translocation of S. Heidelberg by significantly decreasing the expression of Salmonella virulence genes such as sipA. The bioactive fractions also significantly downregulated the flagellar gene fliC, suggesting the involvement of other active molecules. This study showed the interest to characterize better the metabolites produced by B. fragilis to make them means of fighting pathogenic bacteria by targeting their virulence factor without modifying the gut microbiota.